Pengaruh Motivasi dalam Perpsektif Islam terhadap Kinerja Pemasaran pada Bank Syariah Indonesia KCP Muara Bulian - Sumantri Sumantri; Yulia Ningsih; Rama Rizki Dermawan (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2021)
The purpose of this study was to determine the effect of motivation and work discipline in an Islamic perspective on marketing performance at Bank Syariah Indonesia KCP. Bulian Estuary. The analytical method used is quantitative using multiple linear regression analysis tools. Testing the significance of the influence of Motivation (X1) and Work Discipline (X2) as the independent variable and Marketing Performance (Y) as the dependent variable, conducted the T-Test and F-Test. Based on the results of the study, it was found that the tcount Motivation (X1) was 5.867. Because t arithmetic 5.867 > t table 2.120 then Ho is rejected. So it can be concluded that the motivation variable (X1) has a significant effect on marketing performance (Y). Based on the results of the study, it was found that the tcount value of the Discipline variable (X2) was -1.432. Because t count -1.432 < t table 2.120 then Ho is accepted. So it can be concluded that the discipline variable (X2) has no significant effect on marketing performance (Y). Based on the results of the study, it was found that the fcount value was 31.048. It can be interpreted that the Motivation variable (X1) and Discipline (X2) can work together (simultaneously) on the Marketing Performance variable (Y). This is because Fcount > Ftabeel or 31.048 > 3.63 the resulting significant value is smaller than the size of the significant value, which is 0.005. The resulting Adjusted R Square is 0.795. So it can be concluded that the percentage of the influence of motivation and discipline on marketing performance is 79.5% and the remaining 20.5% is influenced by other factors not examined in this study.